2020
DOI: 10.1016/j.apnu.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and risk perception among Italian healthcare workers during the second month of the Covid-19 pandemic

Abstract: A multicentre cross-sectional study was conducted to assess perceived risk and fear of contagion, as well as mental health outcomes among 650 Italian healthcare workers during the COVID-19 outbreak. A relevant proportion of the sample reported symptoms of anxiety, depression, and distress. Female sex, nursing profession, fear of being infected, as well as the time of exposure to the COVID-19 spread and the fact of directly attending infected patients were the main risk factors for developing mental health dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(143 citation statements)
references
References 32 publications
8
126
1
8
Order By: Relevance
“…Stress was estimated in 40 studies [ 18 , 20 , 25 , 27 , 29 , 33 , 35 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. The overall pooled point estimates of prevalence for stress varied between 10% and 84% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stress was estimated in 40 studies [ 18 , 20 , 25 , 27 , 29 , 33 , 35 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. The overall pooled point estimates of prevalence for stress varied between 10% and 84% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence according to the month of data collected was as follows: February: 32% ( n = 14; 95% CI 25–41; I2 = 98), March: 45% (n = 6; 95% CI 37–53; I2 = 96) and April: 50% ( n = 13; 95% CI 35–66; I2 = 98). Seventeen studies [ 20 , 35 , 36 , 39 , 43 , 44 , 46 , 54 , [57] , [58] , [59] , [60] , [61] , [62] , [63] , 67 , 69 ] involving nurses who were working on the frontline showed stress prevalence at 46% (95% CI = 39–54; I 2 = 97), whereas 20 studies including mixed nurses working in the frontline and second line showed the stress prevalence was 42% (95% CI = 31–53, I 2 = 99). Thirteen studies that used the Perceived Stress Scale (PSS) showed a pooled prevalence of stress at 50% (95% CI = 41–59, I 2 = 98), whereas eight studies [ 35 , 45 , [54] , [55] , [56] , 63 , 64 , 67 ] using the Impact of Event Scale-Revised (IES-R) had a pooled prevalence of 50% (95% CI = 37–63, I 2 = 99).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we also found high levels of emotional disturbance related to COVID-19, supporting the idea that, during this pandemic, patients would also benefit from telecounseling and telepsychiatry, which refers to any type of psychological service performed over the internet (i.e., counseling, psychotherapy, psychoeducation) (40). Previous studies reported the psychosocial effects of the COVID-19 pandemic on patients, caregivers, and the general population, demonstrating significant increases of issues related to anxiety, depression, and posttraumatic stress syndrome (2)(3)(4)(6)(7)(8). For example, in China during COVID-19 outbreak, telemedicine mental health services have been used and prioritized for people who are at higher risk of developing severe health complications related to COVID-19, including COVID-19 patients and their families (39).…”
Section: Discussionmentioning
confidence: 99%
“…In December 2019, a new disease, the coronavirus disease 2019 (COVID- 19), emerged in China and rapidly spread over the world, resulting in a global pandemic on March 11, 2020. Scientific literature suggests that COVID-19 is associated with adverse mental health consequences for general population, hospital staff, and patients, leading to dramatic relapses in the healthcare system worldwide (1,2).…”
Section: Introductionmentioning
confidence: 99%